Emergency remote English language teaching and learning: Voices of primary school students and teachers in Kazakhstan. Issue 2 (20th June 2022) - Hajar, Anas; Manan, Syed Abdul
Abstract: This qualitative study documents the experiences of 38 Grade 5 students and their six female teachers from four state‐maintained schools in Kazakhstan teaching/learning English during emergency remote teaching and learning (ERT&L). It was guided by Kearney et al .'s (2012) framework that provides three dimensions that influence individuals' teaching and learning experience when using technological devices: personalisation, collaboration and authenticity . The data collected through online individual interviews and students' drawings suggest that the participants asserted their agentive reflexivity and critical awareness of the advantages and drawbacks of their ERT&L experiences. Several teachers indicated that although ERT&L helped them make financial and professional gains, they had difficulty assessing their students' progress online, and work overload had negative impacts on their well‐being and quality of life. Many students criticised some English teaching practices during COVID‐19, including the allocation of more homework, and lack of co‐operative activities and individual attention. The study has pedagogical implications and provides further evidence of the need for stakeholders to take the well‐being of teachers into account, promote collaboration between different social actors and provide teachers with proper training in the use of online platforms. It also stresses the importance of using participatory research methods involving children to capture their thoughts and interpretation of their emergency remote learning experiences.